Independence and objectivity of internal auditors within provincial governance systems - Geqeza, Awonke; Dubihlela, Jobo (Jurnal Akuntansi dan Auditing Indonesia, 2024)
The study addresses the dearth of research on internal audit activity independence (IAAI) and internal auditors' objectivity within South Africa's (SA) provincial governance systems, despite their crucial role in government department performance. A mixed research approach was employed, using 260 purposely selected participants. Questionnaires, telephone interviews, and focus group discussions were used as data collection instruments. A triangulation of descriptive statistics and thematic analysis was applied to report the findings. The study found that management is not taking timely corrective action based on audit findings and recommendations. Internal auditors have friendship relationships with auditee employees, sectional heads are not cooperating with the internal audit function (IAF), and management has a negative perception of the IAF, viewing it more as a fault-finder than as adding value to the organization. Furthermore, the study's insights offer practical implications for improving internal audit practices within provincial governance systems, thereby facilitating better governance and operational efficiency.